The impact of continuous teacher training based on the flipped classroom on teaching practices and learner performance - Zahra, Amad; Soumia, Tamani; Mohamed, Radid (International Journal of Evaluation and Research in Education (IJERE), 2025)
The study presents the contribution of in-service teacher training based on the flipped classroom on teaching practices and on learner performance. To meet the objective of this research, an experiment was carried out on a sample of five college teachers of two different subjects and 200 learners divided into two groups (experimental and control). The study used teacher observation before and after the training, two evaluative tests with the learners and a questionnaire with the learners at the end of the experiment. We collected the data, analyzed it, then presented and interpreted the results. The results show that the flipped classroom has a positive impact on teachers’ teaching practices and learners’ performance.